On the Question of Inventor(ship) and the DABUS Case - Smerdu, Nina (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
Inventorship has always been attributed to natural persons (only), but the increasing presence of artificial intelligence in research and development, where new, inventive results are created, raises doubts as to whether creativity and invention are truly inherent only to humans. The subject of this chapter is precisely this challenge, posed to the established patent system. First, the concepts of an inventor and inventive contribution are presented, followed by the development theories of patent law. The second part is devoted to the analysis of the DABUS case, the core of the Artificial Inventor project. The latter's goal is to obtain decisions from competent authorities on the possibility and admissibility of naming artificial intelligence as an inventor in a patent application. Decisions of the European Patent Office and patent offices of Germany, the USA and Australia, as well as court decisions in those countries, are presented and analysed. Lastly, new insights into inventor(ship), both in the figure of a natural person and the potential of artificial intelligence, which (for now) is still based on human creativity, are provided.